2009
DOI: 10.1002/cne.22005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of mosaic brain evolution: Morphometric analysis of the developing zebra finch brain

Abstract: In adult zebra finches (Taeniopygia guttata), the telencephalon occupies 64% of the entire brain. This fraction is similar to what is seen in parrots, but many other birds possess a significantly smaller telencephalon. The aim of the present study was to determine the developmental time course and cellular basis of telencephalic enlargement in zebra finches, and then to compare these findings with what is known about telencephalic enlargement in other birds. To this end we estimated the volumes of all major br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 70 publications
3
53
0
Order By: Relevance
“…To test this hypothesis, we computed the fraction of all tectal cells that is proliferative, rather than postproliferative. We have previously used this proliferative zone fraction (PZF) measure to demonstrate species differences in neurogenesis timing (7,9). Here we extend the approach by staining ED7 brains with proliferating cell nuclear antigen (PCNA), a relatively specific marker for proliferating cells (21) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this hypothesis, we computed the fraction of all tectal cells that is proliferative, rather than postproliferative. We have previously used this proliferative zone fraction (PZF) measure to demonstrate species differences in neurogenesis timing (7,9). Here we extend the approach by staining ED7 brains with proliferating cell nuclear antigen (PCNA), a relatively specific marker for proliferating cells (21) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we reasoned that FGF2 injections into ventricles of embryonic chicks should, by analogy to the work in mammals (14), increase telencephalon volume, effectively creating chickens with a telencephalon as large as that of parrots and songbirds (7,9). However, our FGF2 injections did not significantly alter telencephalon development.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…If the brain composition of homing pigeons is represented by the 'developmental constraints theory' (Finlay and Darlington, 1995), we had to expect that changes in the size of one brain structure would be correlated with changes in all other brain structures. Recently, mosaic evolution has been demonstrated for the brain of wild mammals (Barton and Harvey, 2000), bats and whales (Clark et al, 2001) and wild avian species (Iwaniuk et al, 2004;Iwaniuk and Hurd, 2005;Charvet and Striedter, 2009), and it seems to be that mosaic evolution characterises the diversification of avian and mammalian brain composition without excluding domesticated species. Apparently, it is not just the subsystems of the brain that might follow different trends of alteration independently from others but even the left or right parts of a subsystem.…”
Section: Discussionmentioning
confidence: 99%
“…After all, brain development can be studied at several different levels of analysis -ranging from gene regulation to tissue formation -and each level can be considered a «causal mechanism» in its own right. For example, my own research has shown that the expansion of the telencephalon in parrots and songbirds, relative to other birds, is caused by an evolutionary delay in neurogenesis (which increases the number of telencephalic precursor cells; Charvet & Striedter, 2009). We do not know the molecular mechanism underlying this change in neurogenesis timing, but our finding is nonetheless mechanistic.…”
Section: Monographmentioning
confidence: 99%